Genome Sequences and Methylation Patterns of Natrinema versiforme BOL5-4 and Natrinema pallidum BOL6-1, Two Extremely Halophilic Archaea from a Bolivian Salt Mine - DasSarma, Priya (2019)
Two extremely halophilic archaea, namely, Natrinema versiforme BOL5-4 and Natrinema pallidum BOL6-1, were isolated from a Bolivian salt mine and their genomes sequenced using single-molecule real-time sequencing. The GC-rich genomes of BOL5-4 and BOL6-1 were 4.6 and 3.8 Mbp, respectively, with large chromosomes and multiple megaplasmids. Genome annotation was incorporated into HaloWeb and methylation patterns incorporated into REBASE.